Optimization of Student Development Activities to Improve the Quality of Output - Lola Amalia Sibarani; Nurika Khalila Daulay (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study aims to examine the optimization of student training activities to improve the quality of student learning outcomes at SMP Kartika 1-2 Medan. This study uses a qualitative research type with a case study approach. The conclusion of this study shows that the principal and student teachers play an important role in encouraging student training activities to foster student interests and talents. So that it can improve the quality of student output, both academic and non-academic aspects. Student development organized through various activities such as OSIS, Scouts, Paskibra, Dance, Futsal, Learning to Read the Qur'an, and Studying the Al-Kitab (Pa), and religious activities has provided space for students to develop their potential, shape character, improve social skills, and strengthen leadership. These activities are an important means of fostering discipline, a sense of responsibility, and a spirit of collaboration in students, which ultimately contribute to creating quality graduates ready to compete in the future.